Application of a systematic approach to determining the effectiveness of emergency rescue measures during the elimination of emergencies of natural and man-made nature - Romanyuk , Valentin; Meshcheriakov, Ivan; Andriuk , Olena (Social Development and Security, 2020)
The article presents the results of the development of scientific and methodological system approach to assessing the effectiveness of the organizational and technical system of emergency rescue operations during the elimination of natural and man-made emergencies in the area of the Joint Forces operation. Based on the results obtained is observed increasing the integrated efficiency of the use of the resource potential of the organizational and technical system of emergency rescue operations by increasing the functional (systemic) or corresponding economic effect.